COPD in Helsinki, Finland: socioeconomic status based on occupation has an important impact on prevalence. Issue 6 (August 2013) - Kainu, Annette; Rouhos, Annamari; Sovijärvi, Anssi; Lindqvist, Ari; Sarna, Seppo; Lundbäck, Bo
Objectives : Chronic obstructive pulmonary disease (COPD) is globally a major, but often undiagnosed, cause of morbidity and mortality. The aims of this study were to assess the prevalence of COPD in Helsinki, Finland, with international diagnostic criteria and to analyse risk factors including socioeconomic status, and disease severity. Methods : A general population sample of 628 adults (368 women) completed flow-volume spirometry with bronchodilation test and a structured interview. Post-bronchodilation spirometry was assessed both using the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria and relative to the fifth percentile of the reference value (lower limit of normal, LLN). Results : According to GOLD criteria, 37 (5.9%), and by using the LLN criteria, 43 subjects (6.8%) had airway obstruction consistent with COPD. Using the GOLD criteria, four subjects or 0.6% of the population had severe, 3.0% moderate, and 2.2% mild COPD. Of those with post-bronchodilator obstruction, 49% had no previous diagnosis of obstructive airways disease and did not use medication for any respiratory disease. The prevalence of undiagnosed COPD defined by GOLD was 2.9% (LLN 3.3%). In addition to age, smoking history, and prior history of asthma, socioeconomic status based on occupation was significantly related to COPD in the population. Manual workers in industry (GOLD 10.0%, LLN 11.7%) and non-manual assistant employees (10.2%, 10.2%) had a significantly higher prevalence of COPD than professionals (2.8%, 2.3%). Conclusions : Although smoking is the main modifiable risk factor for COPD, the disease was significantly related to manual workers and non-manual assistant employees, i.e. socioeconomic groups reflecting occupation.